Aortic Valve Stenosis: From Basic Mechanisms to Novel Therapeutic Targets. Issue 4 (April 2020) - Goody, Philip Roger; Hosen, Mohammed Rabiul; Christmann, Dominik; Niepmann, Sven Thomas; Zietzer, Andreas; Adam, Matti; Bönner, Florian; Zimmer, Sebastian; Nickenig, Georg; Jansen, Felix
Abstract : Aortic valve stenosis is the most prevalent heart valve disease worldwide. Although interventional treatment options have rapidly improved in recent years, symptomatic aortic valve stenosis is still associated with high morbidity and mortality. Calcific aortic valve stenosis is characterized by a progressive fibro-calcific remodeling and thickening of the aortic valve cusps, which subsequently leads to valve obstruction. The underlying pathophysiology is complex and involves endothelial dysfunction, immune cell infiltration, myofibroblastic and osteoblastic differentiation, and, subsequently, calcification. To date, no pharmacotherapy has been established to prevent aortic valve calcification. However, novel promising therapeutic targets have been recently identified. This review summarizes the current knowledge of pathomechanisms involved in aortic valve calcification and points out novel treatment strategies.